The specter of failed transition : Tocqueville and the reception of liberalism in reform China - van Dongen, Els (2020)
What connects the political thinker and historian Alexis de Tocqueville (1805-1859) to China? Hitherto, scholars have answered this question by looking into references to China in his Democracy in America and The Old Regime and the Revolution or by applying insights from his works to issues of democratization. This article seeks to move beyond these “Tocquevillian perspectives on China” and instead foregrounds “Chinese perspectives on Tocqueville”: How did Chinese thinkers understand Tocqueville in reform China (post-1978)? Building on existing research that has analyzed Tocqueville as a thinker concerned with transition rather than with democratization per se, this article posits that Chinese intellectuals interpreted Tocqueville to warn against the dangers of “failed transition” after the suppression of the Tiananmen demonstrations and the disintegration of the Soviet Union. Swayed by the Tocquevillian paradox of reform, they identified the French and Anglo-American “models” as “cases” from which general lessons could be drawn. The article further posits that the renewed interest in Tocqueville in the 2010s was also marked by the specter of failed transition. Later, readers and officials pinpointed the rise of social inequality as a potentially destabilizing factor. Finally, the article sheds light on these contemporary readings of Tocqueville against the broader background of the history of liberalism in China.